Morphology Of Uninhabited Vehicle Platform Complexity Using Information Theory-based Methods - Kumar, Ajay (Cranfield University, 2022)
Complexity of a dynamical system is defined as a function of the morphology and the information entropy of the system. Structure is an essential property of the dynamical systems, for it to perform functions, by enabling the flow of information in the system. Many times, the structure of the system is not completely known. In such a case, it can be estimated using elements of information theory (Shannon's information entropy, mutual information). The complexity of the system is bounded. The upper bound is uncertainty dominated and relationships between the elements of the system are fuzzy. On the other hand, at the lower bound, the system functions in a deterministic structure-dominated fashion. The robustness of the system is a measure of margins between the current complexity to the critical complexity of the system.
Keywords: Complexity; Information theory; DSDS22 Poster; DSDS22; Uncertainty